Life experiences of mothers of children with intellectual disability - Piroğlu Akçakmak, Gökçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
The purpose of this study is to examine the life experiences of mothers of children with intellectual disability. In order to better understand how the disability of their children affects the mothers and their families better, it aims to give voices to mothers’ stories from the pregnancy period to present by examining from the aspects of their experiences before and after the diagnosis of their children, their knowledge and needs about the disability, their mothering role in daily life, relationship with their family and society and also positive aspects of the disability in their lives. Nine mothers whose children have intellectual disability were individually interviewed for this research study by means of in-depth interviews. Additionally, they were given demographic forms before the interview took place. The children were between 7 to 15 years old. Children were all diagnosed with mild intellectual disability at least 5 years ago and they were in inclusive educational settings and also they were eligible to receive special educational services from rehabilitation centers in İstanbul. All mothers in this study were housewives and they were from low to middle socioeconomicalstatus and from primary to higher educational level. Data obtained from interviews were analyzed by using thematic method. Findings showed that being the mother of a child with intellectual disability was not only challenging but also pleasant for these mothers. Although they stated that they were tired due to the combination of needs mothers should fulfill for their children and the whole family, they were also happy to have a child with special needs from whom they learned different ways of living. They also emphasized their needs of support and how they were worried about the future of their children with disability after they would decease. Moreover, mothers were complaining about the discrimination in social and educational settings toward children with disability and how this negative attitude affected their lives. The analysis of the data also indicated that mothers of children with intellectual disability had various problems in family and social life. Emotional stress of having a child with disability, discrimination of the child due to his or her disability, daily requirements of a mother at home, neglecting of other siblings and social life had pressure on these mothers. Due to these reasons, they expressed that they had lots of stressors in their life.
Keywords: Parents of children with disabilities.